Pembuatan Peta Desain Tapak KUPS Wisata KTH HKm Sukkuru Mappoji - H Harmudinsyah; Akbar Fuad Husain (Jurnal Pengabdian Masyarakat Hasanuddin (JPMH), 2022)
Padang Loang, Botto Lai, is one of the areas in the Coppo Village which contains a Community Forest area called Sukkuru Mappoji. Within the forest area, there are areas that have not been developed and have the potential to become tourist KUPS. The location has the potential for waterfall tourism and a stretch of nature with a view of the City of Barru. Members of the Sukkuru Mappoji HKm Farmers Group do not yet have a site plan map that can be used as a guide in realizing the "tourism". The service method is carried out in three stages, namely a site survey, the design process, and the presentation of the design results. The resulting output is in the form of a site design map of the KTH HKm Sukkuru Mappoji KUPs tourism site. The results of the site design will later be very important for members of the Sukkuru Mappoji HKm in order to realize it in the field and the implementation of a tourism KUPS that can "become a new source of livelihood for them."